Improving meal context in nursing homes. Impact of four strategies on food intake and meal pleasure. (1st January 2015) - Divert, Camille; Laghmaoui, Rachid; Crema, Célia; Issanchou, Sylvie; Wymelbeke, Virginie Van; Sulmont-Rossé, Claire
Highlights: Changing a single contextual element could impact food intake in nursing homes. Food contextual factors impact meal enjoyment and food intake in nursing homes. Non-food contextual factor did not impact food intake in nursing homes. Proposing two vegetables instead of one increased meat consumption in the elderly. The bigger the portion, the more is eaten by institutionalized elderly. Institutionalized elderly eat less when free to choose the portion size. Abstract: In France, in most nursing homes, the composition of menus, the time and the place at which meals are served, the choice of one's place at the table are imposed on residents. Yet, the act of eating cannot be restricted to nutritional and sensory aspects alone. It also includes a psycho-affective dimension, which relates to the context in which the meal is served. We tested the impact of four contextual factors, considered individually, on food intake and meal pleasure in elderly people living in nursing homes: the way the main course was named on the menu, the size and the variety of portions of vegetables served to residents, the presence or not of condiments in the middle of the table and the presence or not of elements to modify the surroundings such as a decorative object on the table or background music. Twelve experimental meals were served to 42 nursing home residents. For each factor, we compared a control condition with two experimental conditions. Our study showed that changing a single contextual element of the meal in nursing homes could be sufficient to improve residents' satisfaction with their meals and increase the quantities of meat or vegetables consumed, as long as this factor had a direct impact on what was going to be consumed (increased variety on the plate, condiments on the table). Factors affecting the context of the meal (names of dishes, decor) proved to be ineffective. Given the budgetary constraints faced by nursing homes, this study proposes interesting and inexpensive ideas to increase satisfaction with meals and food intake in elderly people who are dependent on others for their meals.